Proposal for a didactic unit of Olympic Wrestling: World Wrestling (Revista de Artes Marciales Asiáticas, 2018)
Wrestling is a natural human activity and it is represented in a large number of countries and cultures. In secondary education, combat sports can help students develop relevant skills and attitudes. Wrestling exercises develop motor, perceptual and affective capacities, since wrestling is a close contact sport. The objective of this work was to design a bilingual teaching unit aimed at the secondary education, where wrestling exercises are used to achieve educational purposes related to learning Olympic Wrestling and fostering situations of communication in English. The didactic unit, called Luchas del Mundo / World Wrestling, will have a recreational and integrative character, and will allow students to relate and communicate with their peers in English during the practical sessions. The didactic unit consists of six sessions, making a journey through different continents and wrestling styles, and finishing with the Olympic wrestling styles. All sessions will follow a similar scheme, starting with a general and specific warm up; following with the main part, in which representative wrestling exercises will be practiced (grips, holds, unbalancing, etc.); and finishing with a cool down, stretches and conclusions. In summary, this proposal follows the contents worked in primary education physical education and tries to promote the practice of Olympic Wrestling in secondary education.